Pokémon Go: the dawn of global augmented reality - Sousa, Ivo Dias de (2017)
Pokémon Go is considered the most popular game ever for smartphones. It has more daily users than the social network Twitter. In the United States, on the first week, more than 10% of mobile phones with Android downloaded the game. The numbers are amazing. Pokémon Go is a sort of virtual geocaching. The relation that the game establishes between the virtual world and the real world is well done, relying on the connection to Google Maps. People recognize the places displyed on their mobile phones and “believe” the pokémons are there.